Pengaruh Transformational Leadership Terhadap Financial Performance Dengan Supply Chain Integration dan Competitive Advantage sebagai Variabel Intervening Pada Perusahaan Publik Sektor Manufaktur Di Surabaya Dan Sidoarjo - Michellie - Devinsen; Devie Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the significantly direct and positive affect of transformational leadership to competitive advantage, transformational leadership to supply chain integration supply chain integration to financial performance, competitive advantage to financial performance, on go public manufacturing firms in Surabaya and Sidoarjo. This study used quantitative approach, and the data obtained through the distribution of questionnaires and used ratio financial statement analysis to go public manufacturing firms in Surabaya and processed by using SmartPLS software. This study showed that there was a positive and significant relationship of transformational leadership to financial performance, transformational leadership to supply chain integration, transformational leadership to comeptitive advantage, supply chain integration to competitive advantage, supply chain integration to financial performance and competitive advantage to financial performance on go public manufacturing firms in Surabaya and Sidoarjo. Supply chain integration and competitive advantage became the intervening variables to transformational leadership and financial performance.